Gender Differences in Affective and Evaluative Responses to Experimentally Induced Body Checking of Positively and Negatively Valenced Body Parts - Tanck, Julia A.; Vocks, Silja; Riesselmann, Bettina; Waldorf, Manuel (Frontiers in Psychology, 2019)
Body checking (BC) is defined as behavior aimed at gaining information on body shape, size, or weight. Besides its occurrence as a transdiagnostic symptom in eating disorders (ED), BC is widespread in nonclinical populations. It is associated with body dissatisfaction and the de-velopment of body image disturbances and ED. Males and females differ in terms of body dissatisfaction and associated BC strategies. However, the question of a gender-related inten-sity of negative affect and state body satisfaction as reactions to BC remains open. Therefore, the present experimental study aimed to examine gender differences in affective and evalua-tive responses to BC. We tested n = 60 women and n = 60 men in a crossover design, imple-menting two experimental conditions and one control condition. In the negative body check-ing condition (NBC), participants received standardized instructions to check negatively va-lenced body parts. In the positive body checking condition (PBC), by contrast, participants were asked to check positively valenced body parts. The control condition (CBC) consisted of playing a computer game. Before and after checking of one’s own body, participants rated negative body-related affect, i.e., guilt, shame, and disgust, and state body satisfaction. The results indicate that both NBC and PBC led to an increase in negative affect for men and women. Eating pathology predicted negative affect after checking in NBC for both genders. Men reported a significantly higher state body satisfaction in all conditions, whereas only women showed decreased body satisfaction in NBC. These findings suggest that BC of any body part (i.e., positively or negatively valenced) leads to increased negative affect for both genders. Eating pathology significantly influences the affective responses to BC for both gen-ders. Changes in state body satisfaction, however, only occur in females. An explanation might be that men generally report higher body satisfaction, resulting in a more stable body image. Females and males with pathological eating behavior seem to be more vulnerable to changes in negative affect. As negative affect is equally increased after NBC and PBC for both genders, BC might play a central role in the maintenance of body image disturbances in males and females.